Trefftz type method for 2D problems of electromagnetic scattering from inhomogeneous bodies - Reutskiy, S. Yu. (Computer Assisted Methods in Engineering and Science, 2023)
A new numerical method for scattering from inhomogeneous bodies is presented. The cases of E and H-polarizated incident wave scattered by an infinite 2D cylinder are considered. The scattered field is looked for in two different domains. The first one is a bounded region inside the scattering body with an inhomogeneous permittivity Ɛ:(x, y). The second one is an unbounded homogeneous region outside the scatterer. An approximate solution for the scattered field inside the scatterer is looked for by applying the QTSM technique. The method of discrete sources is used to approximate the scattered field in the unbounded region outside the scattering body. A comparison of the numerical and analytic solutions is performed.